Defining clavicle growth in infancy using chest radiographs - Hadamek, Yvonne; Krueger, Paul-Christian; Mentzel, Hans-Joachim; Waginger, Matthias (Frontiers in Pediatrics, 2024)
Background Despite the critical role of the clavicle in understanding growth and development in early childhood, there remains a notable paucity of comprehensive studies investigating clavicle growth patterns during this crucial period. This hinders our ability to establish normative growth parameters during these early life stages. Our study sought to measure clavicle dimensions and subsequently construct growth curves spanning from preterm infants to toddlers up to the age of 6 years by measuring routine chest radiographs. Differences between both sides of the body and between the sexes should be analysed. This aimed to provide a nuanced understanding of clavicle growth dynamics and offering a foundation for the establishment of normative values in this understudied context. In this retrospective study, children aged 23 weeks of gestation to 6 years who underwent a chest radiography between January 2010 and June 2020 were enrolled. A total of 5.311 potential radiographs was screened. Clavicle length and width were measured in all radiographs using the Centricity™ Universal Viewer. Statistical analysis was performed using SPSS®. Results 1.340 images met the quality criteria to be included in our study. The growth curves of clavicle lengths and widths showed a steadily increasing trend with age. Inclusion of premature infants in the age group of one month resulted in a decrease in this age group. Significant differences between both sides of the body and between the sexes could be shown. Measurements of clavicle length and width, derived from routine chest radiographs, are highly accurate. This accuracy underscores the potential for utilizing thoracic radiographs as a reliable tool for assessing clavicle growth in clinical settings or even forensic analysts. The establishment of reference values derived from our measurements provides a basis for normative growth parameters.